Security designs for the cloud, IoT, and social networking - Le, Dac-Nhuong, 1983-; Bhatt, Chintan M., 1988-; Madhukar, Mani (Hoboken, New Jersey : John Wiley & Sons, Inc. ; Salem, Massachusetts : Scrivener Publishing LLC, 2019)
"Security concerns around the rapid growth and variety of devices that are controlled and managed over the Internet is an immediate potential threat to all who own or use them. This book examines the issues surrounding these problems, vulnerabilities, what can be done to solve the problems, investigating the roots of the problems and how programming and attention to good security practice can combat the threats today that are a result of lax security processes on the Internet of Things, cloud computing and social media"--
13 Optimization of Ontology-Based Clinical Pathways and Incorporating Differential Privacy in the Healthcare System14 Advancements and Applications in Fog Computing; 15 Taxonomy of Cyber-Physical Social Systems in Intelligent Transportation; 16 Cyberspace for Smart Parenting with Sensors; EULA
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
John Wiley and Sons
Keywords: Cloud computing -- Security measures; Internet of things -- Security measures; Social media -- Security measures; Infonuagique -- x; Internet des objets -- x; x -- Mesures; Cloud computing -- Security measures